'More collaborative and open': As systemic psychotherapists become more familiar with videoconferencing, are the advantages of the medium becoming more apparent? A focus group study with UK systemic practitioners. Issue 2 (6th May 2022) - Burbach, Frank R.; Stiles, Katie M.; Brown, Katherine; Allen, Victoria M. E.; Mc Kenny, Richard
Three semi-structured online focus group interviews were conducted with 17 systemic psychotherapists in the UK 1 year after the transition to videoconferencing therapy (or 'teletherapy') prompted by the COVID-19 pandemic. Thematic analysis identified 23 themes within 10 superordinate themes including Advantages of working online; Changes to the therapeutic relationship; Comparison to in-person therapy; Using therapeutic techniques online; Disadvantages of working online; Adapting to the affordances and constraints of technology. Whilst experiences were mildly positive overall, participants responded with almost twice as many positive comments as negative ones and described themselves as likely to continue working online. This study explores the advantages of online delivery which were described in the focus groups and posits that these digital affordances will lead to the development of more collaborative and invitational approaches.